2017
DOI: 10.1093/molbev/msx090
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Domain Architecture, Structure, and Ligand Affinity in Animal and Plant RNA-Binding Proteins

Abstract: Reconstruction of ancestral protein sequences using phylogenetic methods is a powerful technique for directly examining the evolution of molecular function. Although ancestral sequence reconstruction (ASR) is itself very efficient, downstream functional, and structural studies necessary to characterize when and how changes in molecular function occurred are often costly and time-consuming, currently limiting ASR studies to examining a relatively small number of discrete functional shifts. As a result, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 114 publications
3
17
0
Order By: Relevance
“…The addition of new sequence data, alignments and tree inference strategies in the current analysis further reinforced the major features of our previously inferred phylogeny, arguing in favor of its general robustness. Our previous studies suggest that Argonaute (AGO) and double-stranded RNA-binding protein (DRB) phylogenies exhibit similar patterns of duplications and losses as our Dicer tree ( Mukherjee et al 2013 ; Dias et al 2017 ), suggesting a general model in which major components of the RNA interference pathway may have duplicated in early animals, with the duplicate pathway being retained only in the arthropod lineage. Of course, new sequence data or major advances in phylogenetic methods could alter our current view of Dicer evolutionary history.…”
Section: Resultsmentioning
confidence: 56%
“…The addition of new sequence data, alignments and tree inference strategies in the current analysis further reinforced the major features of our previously inferred phylogeny, arguing in favor of its general robustness. Our previous studies suggest that Argonaute (AGO) and double-stranded RNA-binding protein (DRB) phylogenies exhibit similar patterns of duplications and losses as our Dicer tree ( Mukherjee et al 2013 ; Dias et al 2017 ), suggesting a general model in which major components of the RNA interference pathway may have duplicated in early animals, with the duplicate pathway being retained only in the arthropod lineage. Of course, new sequence data or major advances in phylogenetic methods could alter our current view of Dicer evolutionary history.…”
Section: Resultsmentioning
confidence: 56%
“…Ever since that time it has been widely accepted that this was the correct explanation for the origin of the NylB enzyme. 12,13,14,15,16,17 It has been widely assumed that this happened in an extremely short timeframe, soon after the invention of nylon in 1935. Some people, by extension, have assumed that Ohno's frameshift claim might help explain other nylonases such as NylA and NylC.…”
Section: Discussionmentioning
confidence: 99%
“…Further, various fungal groups also exhibit the presence of Dicer and plant-like DSRM proteins and lack animal-like accessory proteins, such as Drosha and Pasha (Dang et al, 2011;Dias et al, 2017).…”
Section: Hyl1la Regulates the Mirna Biogenesismentioning
confidence: 99%
“…Additionally, we also could not find any homologs in bilaterian animals and in unicellular organism like Fungi and Ichthyosporea. However, deep phylogenetic study of DSRM proteins showed that the protozoans and fungi are phylogenetically closer to the DSRM protein of plants (Dias et al, 2017).…”
mentioning
confidence: 99%